2010
DOI: 10.1186/ar3067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inflammatory cytokine IL-27 on the activation of fibroblast-like synoviocytes in rheumatoid arthritis

Abstract: IntroductionInterleukin (IL)-27 is a novel member of the IL-6/IL-12 family cytokines that are produced early by antigen-presenting cells in T helper (Th)1-mediated inflammation. Elevated expression of IL-27 has been detected in the synovial membranes and fluid of rheumatoid arthritis (RA).MethodsWe investigated the in vitro effects of IL-27, alone or in combination with inflammatory cytokine tumor necrosis factor (TNF)-α or IL-1 β on the pro-inflammatory activation of human primary fibroblast-like synoviocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 60 publications
(73 reference statements)
5
82
0
1
Order By: Relevance
“…27 We have recently reported that the inflammatory cytokine IL-27 can activate FLS in RA by activating distinct intracellular signaling pathways. 11 The present study further revealed that uric acid plays a crucial role in provoking inflammation by activating FLS through intracellular signal transduction mechanisms in RA.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…27 We have recently reported that the inflammatory cytokine IL-27 can activate FLS in RA by activating distinct intracellular signaling pathways. 11 The present study further revealed that uric acid plays a crucial role in provoking inflammation by activating FLS through intracellular signal transduction mechanisms in RA.…”
Section: Discussionsupporting
confidence: 64%
“…11 Intracellular staining of activated (phosphorylated) signaling molecules The intracellular expression of phosphorylated signaling molecules was determined quantitatively using previously established intracellular staining methods using flow cytometry. 11,22 This quantitative flow cytometric method for the analysis of the activation of intracellular signaling molecules by intracellular staining of phosphorylated signaling molecules is less tedious than western blot, and the flow cytometric method requires fewer cells and a reduced assay time. Briefly, cells were fixed with pre-warmed BD Cytofix Buffer (4% paraformaldehyde) for 10 min at 37 uC following stimulation by monosodium urate crystals.…”
Section: Assay For Human Il-6 Cxcl8 and Mmp-1mentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with these findings, anti-IL-27 antibody treatment or IL-27 receptor knockout has been found to suppress ongoing severe inflammation and proinflammatory cytokine production in AIA (5). Moreover, recently published data suggested that IL-27 could stimulate other nonimmune cell targets, such as fibroblast-like synoviocytes (FLS), in the joints and induce the expression of adhesion molecules on the cell surface of FLS and the release of chemokines and MMP-1 in RA FLS (6,7).…”
Section: To the Editormentioning
confidence: 99%